Analysis of Airport Operation Control Center (AOCC) Unit Services at Adi Soemarmo Boyolali International Airport - Aeni, Fadzillah Ika Nur; Novianty, Rezty Fauziah (CV. Rayyan Dwi Bharata, 2024)
Airport Operation Control Center (AOCC) is the front line in supervising and controlling all problems and is the control center of Adi Soemarmo Solo International Airport operations in serving Airport Service Users. AOCC involves all stakeholders at the Airport by integrating the systems owned by each stakeholder so that they can operate effectively and efficiently. This study aims to determine how the AOCC unit service system is at Adi Soemarmo Boyolali International Airport and what factors can cause problems and solutions to AOCC unit service problems. This study uses a descriptive qualitative approach. The data used are primary and secondary data. Primary data is obtained from observation and interviews, while secondary data comes from literature studies and photographs related to the problems studied. The data analysis techniques used are data reduction, data presentation and drawing conclusions. To test the validity of the data, triangulation techniques are used. The research time is in August - September 2023. The results of this study indicate that a good service system was found by the Airport Operation Control Center (AOCC) Unit to service users starting from coordination with all parties, namely Airlines and Ground Handling, Air Traffic Control (ATC), Apron Movement Control (AMC), Information Unit, Aviation Security, Airport Operation Landside And Terminal (AOLT), Traffic Administration Office and Central Flight Schedule Office (CFSO) and the Airport Mechanical Unit. The service system uses the ACDM (Airport Collaborative Decision Making) system, namely with collaboration between stakeholders to share information between related parties in real time and make joint decisions in a win-solution manner. Factors that can cause problems are related to coordination between one and another so that it can harm several parties. The solution to various problems is to implement ACDM (Airport Collaborative Decision Making), where related units in airport operations synergize with each other, receive and share information from each unit, make proactive and appropriate joint decisions, anticipate unexpected events and provide the best quality of service, cohesiveness and unity of vision and mission.